Theoretical and Methodological Approaches to the Statistical Support of the Structural Transformations in the Economy - Zakhozhai, V. B.; Savytskyi А. V. (Statistics of Ukraine, 2025)
challenges of today caused by the aggravating economic crisis in Ukraine, numerous threats to the national security, in particular the ones resulting from invasion and occupation of the Ukrainian territory by the Russian army, massive destruction of the national economy are the evidence of the need in revision, elaboration and development of efficient structural transformation processes in the Ukrainian economy. This involves the need in devising and implementing an adequate information and analytical support that would allow to set up tactical and strategic dimensions of this reconstruction. This determines the relevance of the research topic. The research objective is to highlight the meaning of the notions “structure”, “structural shifts”, “structural crisis”, “transformation”, “transformation process”, “structural transformation’, to reveal their common and distinct features, to outline the criteria of the efficiency of structural shifts and ways of enhancing the structural transformation processes in Ukraine, and to describe their assessment techniques. The objective was achieved using empirical, theoretical and complex methods of statistical research: observation, comparison, abstraction, analysis and synthesis, formal logic, analogy and deduction. The importance of information and analytical support at each hierarchical level of economic management, from business enterprise to macro-economy, is demonstrated. A series of meaningful approaches are given, with proposing to use them, depending on the need and circumstances, either separately or in various combination or as an integrated set. Characterizations of existing types of assessment from the qualitative and quantitative perspective allowed to give descriptions of their statistical algorithms, and to substantiate the feasibility of the universal approach based on a universal metric. It enables to assess qualitative and quantitative parameters of transformations, determine their efficiency, and (in case of need) to rank the objects under study. The practical value of this article is that the proposed techniques can be used in the decision-making process pertaining to structural transformations in Ukraine at all the hierarchical levels of economic management, from business entities to the macro-economy.